Правосвідомість особи як передумова її правомірної поведінки: ретроспективний погляд, сучасна інтерпретація - Шульга, А.М.; Shulga, A.M.; Anatolii Shulha (Право і безпека. – 2022. – № 4 (87). – С. 45-58, 2022)
Досліджено основи правосвідомості як передумови правомірної поведінки особи. Зазначено, що поняття «правосвідомість» розуміється широко, ним охоплюється і усвідомлюване, і неусвідомлюване у правовій сфері внутрішнього світу людини. Звернено увагу, що в контексті логіки формування механізму внутрішньої детермінації правомірної поведінки у структурі правосвідомості особи умовно може виокремлюватися статична частина (знання права) і динамічна частина, тобто мотивація правомірної поведінки особи, яку слід відрізняти від психологічного механізму дії права, механізму прийняття особою правозначущого рішення, механізму свідомо- вольової правозначущої поведінки особи. Зазначено, що розрізнення мотивації свідомо ї правомірної поведінки і мотивації об’єктивно правомірної поведінки особи вказує на існування таких явищ,як квазіправосвідомість, квазіюридична мотивація.

The basics for legal consciousness as a prerequisite for lawful behavior of a person have been investigated. It has been noted that in today’s conditions the term “legal consciousness” is understood broadly, it covers, which is paradoxical or insufficiently correct from a critical point of view, both conscious and unconscious in the legal sphere of the inner world of man, that is, there is a need to distinguish between the concepts of “legal consciousness” and “legal subconsciousness”. It has been noted that in the context of the logic of formation of the mechanism of internal de-termination of lawful behavior in the structure of legal consciousness of a person, static and dynamic parts can be conditionally distinguished. The statics of legal consciousness is embod-ied by legal awareness (“knowledge of law”) as a psychological basis for the conscious implementation of legal norms. The dynamic element is understood as a certain generalized internal driving force (conscious, unconscious) that leads to the objectification of lawful behavior. The dynamics of legal consciousness is embodied by the motivation of lawful behavior (“lawful motivation”). The motivation of a person’s lawful behavior should be distinguished from the psychologi cal mechanism of the law, the mechanism of making a lawful decision by a person, the mechanism of conscious-willful lawful behavior of a person, while the motivation is not reduced to motives as a certain set (set) of them. Distinguishing between the motivation of con-scious lawful behavior and the motivation of objectively lawful behavior of a person indicates the existence of such phenomena as quasi-legal consciousness, quasi-legal motivation.It has been emphasized that a variant of debatable terminology that reflects the psychological mechanism of law is the phrase “negative motives” and “positive motives”. It has been noted that lawful behavior as a fact can be motivated and unmotivated, but unmotivation does not mean the absence of a motive, but its unconsciousness. Accordingly, it is necessary to distin-guish between conscious in lawful behavior and unconscious in lawful behavior (legal attitudes, habits, skills, legal intuition). The socalled fixed attitudes as an internalprerequisite for lawful behavior are unconscious, while social attitudes can be conscious. Legal attitudes are the basis for legal value orientations. It has been noted that the concept of “sense of law” as an ele-ment of motivation of lawful behavior is actually identical to the concept of “legal intuition”, which as a result of legal socialization of a person is at the same time their moral intuition. It also has a connection with the legal mentality of a person.

Исследованы основы правосознания как предпосылки правомерного поведения личности. Отмечено, что в условиях современности понятие «правосознание» понимается широко, им охватывается и осознаваемое, и неосознаваемое в правовой сфере внутреннего мира человека. Обращено внимание, что в контексте логики формирования механизма внутренней детерминации правомерного поведения в структуре правосознания личности условно можно различать статическую часть (знание права) и динамическую часть, то есть мотивацию правомерного поведения личности, которую следует отличать от психологического механизма действия права, механизма принятия личностью правозначимого решения, механизма сознательно-волевого правозначимого поведения личности. Указано, что различие мотивации сознательного правомерного поведения и мотивации объективно-правомерного поведения личности указывает на существование таких явлений, как квазиправосознание, квазиюридическая мотивация.
Legal consciousness as a prerequisite for person ’s lawful behavior: retrospective view, modern interpretation
Правосознани е личности к ак предпосылка её правомерного поведения: ретроспективный взгляд, современная интерпретация
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; правосвідомість особи; legal awareness of a person; правосознание личности; статика правосвідомості; statics of legal consciousness; статика правосознания; динаміка правосвідомості; dynamics of legal awareness; динамика правосознания; неусвідомлювана правомірна мотивація; unconscious legitimate motivation; неосознаваемая правомерная мотивация; правомірна поведінка; lawful behavior; правомерное поведение